2010
DOI: 10.1007/s12230-010-9172-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of Rhizoctonia solani on Stems, Stolons and Tubers of Potato II. Efficacy of Chemical Applications

Abstract: Fungicide treatments have proven successful in reducing Rhizoctonia solani lesions on stems and stolons; as well as black scurf on tubers. Field studies in Parma and Aberdeen, Idaho, were conducted in 2004 and 2005 to compare the relative effectiveness of in-furrow and seed treatments for disease control on stems, stolons and tubers. The effectiveness of each fungicide placement was evaluated for control of seed-borne and soil-borne inoculum. The systemic fungicide azoxystrobin was used as the in-furrow fungic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, we found that the inoculant RU47 was not able to compensate the negative effect of the pathogen on MTY of potato. Compared to R. solani AG1-IB on lettuce which does not colonize the roots, R. solani AG3 was previously reported to affect all belowground parts of potato including the roots during the growth period ( Atkinson et al, 2011 ; Genzel et al, 2018 ). Thus, it was not surprising that R. solani AG3 had a more pronounced effect on the composition of the bacterial community in the rhizosphere of potato as indicated by the higher d- values than R. solani AG1-IB on the rhizosphere bacterial community in lettuce.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that the inoculant RU47 was not able to compensate the negative effect of the pathogen on MTY of potato. Compared to R. solani AG1-IB on lettuce which does not colonize the roots, R. solani AG3 was previously reported to affect all belowground parts of potato including the roots during the growth period ( Atkinson et al, 2011 ; Genzel et al, 2018 ). Thus, it was not surprising that R. solani AG3 had a more pronounced effect on the composition of the bacterial community in the rhizosphere of potato as indicated by the higher d- values than R. solani AG1-IB on the rhizosphere bacterial community in lettuce.…”
Section: Discussionmentioning
confidence: 99%
“…Wilson et al (1999) reported effectiveness of seed dressing treatments on the severity of common scab using fluazinam, mancozeb and other active ingredients. Similarly, Atkinson et al (2011) verified that seed potato treatments by mancozeb combined with fludioxonil and in-furrow application of azoxystrobin are measures that significantly reduce symptoms of Rhizoctonia stem canker and black scurf. However, more reliable strategies for direct protection than the two mentioned above are currently unavailable.…”
Section: Introductionmentioning
confidence: 72%
“…The incidence and severity of black scurf were not modified. Especially mancozeb, being relatively effective against black scurf (Atkinson et al 2011), was not effective against the disease in any tested foliar applications of the five commercial fungicides in which it was an ingredient. The foliar application comes probably too late and the chemical is more dispersed in the soil in comparison with cited seed dressing treatment, which principally reduces the initial growth of the fungus by effective concentration of active ingredient.…”
Section: Effects Of Fungicidesmentioning
confidence: 87%